Trace Detection of Pb(II) using Square Wave Anodic Stripping Voltammetry with Stainless Steel Electrodes - Sendika Harrista; Muhammad Zamhari; Adinda Fara Aulia; Safina Nur Faizah; Tawatchai Kangkamano (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Lead (Pb(II)) is well known as a dangerous environmental contaminant that harms public health worldwide. Early Pb(II) detection before release into the water system is important. This work describes an inexpensive Pb(II) determination using 5 mm diameter stainless steel rod type 304 as a working electrode. Using a batch system, the research employed 10 mL of 0.1 M acetate buffer at pH 4.5. The best operation was at a deposition potential of -1.2V for 300 s. It provides a linear range in the concentration range of 0.075 – 1 µg/mL Pb(II) (r = 0.994). The limit of detection (LOD) and limit of quantification (LOQ) of Pb(II) were at 0.057 µg/mL and 0.189 µg/mL, respectively. Repeatability and reproducibility were expressed in the relative standard deviation range of 1.26-3.71% in the testing a Pb(II) concentration range of 0.2-1.0 µg/mL and 5.32% in testing a Pb(II) concentration of 0.4 µg/mL. A very low-cost stainless-steel electrode proposed a high operational stability up to 10 measurements with RSD of 4.39%.